Effect of mergerson efficiency and productivity : Some evidence for banks in Malaysia - Awang Marikan, D. A.; Radam, Alias; Baharom, A.H; Ismail, Farhana (Munich Personal RePEc Archive, 2008)
This study is undertaken to investigate the extent to which mergers lead to efficiency by which services are provided to the public and the productivity of Malaysia’s banking institutions sector. The data cover the period 1993 to 2004, which includes the pre-merger years and the post-merger years. This study attempts to evaluate technical efficiency, efficiency change, technical change and productivity of commercial banks, finance companies and merchant banks using a non-parametric Data Envelopment Analysis (DEA) and Malmquist Index approach as the framework for the analyses. It is found that: (1) that on average, productivity across banking institutions increased at annual rate of 5.8% over the study period 1993 to 2004 ; (2) the results also indicated that almost all of the productivity growth comes from technical change (or innovations in banking technology) rather than improvement in efficiency change, which contributes for 6.1% of productivity growth, while the latter accounted for 0.2% decline; (3) the merger process led to productivity improvements whereby, it is observed that the productivity of Malaysia’s banking sector has been improved (in terms of efficiency) after the implementation of merger program for domestic banking institutions in 1999. This might be due to the utilization of their scale economies to improve their efficiencies. However, the productivity of banking institutions has been affected by certain economic conditions in year 2001 and 2004 (such as the September 11 tragedy and the process of capital rationalization that merged entities have undergone)